A generic and dynamic measure of health-related quality of life across a variety of health and disease conditions: insights from healthy individuals and patients with a variety of diagnoses - Mohamad Adam Bujang; Wei Hong Lai; Xun Ting Tiong; Alex Ren Jye Kim; Masliyana Husin; Yvonne Yih Huan Jee; Nurul Fatma Diyana Ahmad; Clare Hui Hong Tan; Khoo Sing Yee; Yoon Khee Hon; Cheng Hoon Chew; Eileen Pin Pin Yap; et al. (BMC Research Notes)
Abstract Objectives Health-Significant Quality of Life Measure (Health-SigQOLM) provides a generic and dynamic assessment of Health-related quality of life (HRQOL). This study aims to assess the HRQOL among healthy and non-healthy participants with varying chronic diseases. Results Comparisons between healthy and non-healthy participants revealed statistically significant differences (p < 0.001) in the mean overall HRQOL score as well as across all its nine domains. Therefore, the Health-SigQOLM, along with its nine domains, is demonstrated to have adequate sensitivity in distinguishing between healthy and non-healthy study participants. This had supported the evidence that the Health-SigQOLM is a reliable and valid scale for measuring both generic and dynamic HRQOL.